TODAY'S ROUND OF THE BOLOGNA PROCESS: CONTINUED OPTIMISM. AND A LITTLE BIT ABOUT RUSSIAN (Paper 1) - V. I. Baidenko; N. A. Selezneva (Высшее образование в России, 2017)
The proposed three-paper series is the authors' attempt to address at least tangentially the whole diversity of quality assurance practices in higher education, the way this diversity has been dynamically manifested and comprehended at the eleven European Quality Assurance Forums (2006-2016). Of course, the authors' intention is to reflect this collective conceptual and methodological activity in the context of the Bologna Process, which obviously has already gone through an optimistic round of its first decade and entered into a contradictory, multi-speed and multilevel reality of transition to the institutional level of reforms.The first article deals with some issues of the current stage of Bolognatransformations amid financial, economic and demographic crisis. The authors briefly touch upon a great potential of Russian higher education, which in late 20 century - early 21st century they described as "Russian pre-Bologna".